Reflections on the Avkat Archaeological Project: collaborations, education, and dissemination - Newhard, James; Elton, Hugh; Haldon, John (Journal of Greek Archaeology, 2020)
The Avkat Archaeological Project took place in Turkey between 2006 and 2010. Like many modern projects, it attempted to shed some light on rural, elite, and non-elite systems of the Medieval period in the eastern Mediterranean. The fieldwork of the project is now over and a publication has been produced. Here we want to discuss a much more reflective, indeed, rather biographic, set of observations about the Avkat Archaeological Project.